DIAGNOSIS OF PCOS IN WOMEN OF EARLY REPRODUCTIVE AGE USING THE DEVELOPED COMPUTER PROGRAM - Светлана Ивановна Елгина; Анжелика Юрьевна Беглова (The Publishing House Medicine and Enlightenment, 2023)
The purpose of the study - to develop a computer program for the diagnosis of polycystic ovary syndrome in women of early reproductive age. Material and methods. The object of the study was 400 women from 18 to 35 years old. The women were divided into two equal groups, taking into account the presence or absence of polycystic ovary syndrome, examined by clinical anamnestic, laboratory, ultrasound and statistical methods. Statistically significant differences between the main indicators characterizing the ovarian reserve in women of early reproductive age with polycystic ovary syndrome and healthy ones have been established. Based on the information base obtained, a computer program was developed using the logistic regression method to diagnose factors and isolate markers that diagnose polycystic ovary syndrome, which was tested on an independent sample. The sensitivity of this method of diagnosing CSF was 87.9 %, and the specificity was 83.6 %. Results. The computer program «Clinical, anamnestic, laboratory and ultrasound diagnostics of polycystic ovary syndrome» was developed and registered (certificate of state registration of the computer program No. 2019662249, date of state registration in the register of computer programs 19.09.2019. Federal Service for Intellectual Property, Moscow). Conclusion. The program for the diagnosis of PCOS «Clinical-anamnestic, laboratory and ultrasound diagnostics of polycystic ovary syndrome», based on the determination of the clinical-anamnestic factor, laboratory and ultrasound markers, can be recommended for routine use for the diagnosis of PCOS and a more differentiated approach to the implementation of therapeutic measures. Early diagnosis and an individual approach to the management of patients with PCOS is necessary for the possibility of selecting treatment, predicting the course of the disease.